Design and assembly of an IoT-based device to determine the absorbed dose of gamma and UV radiation (2023)
Ionizing and non-ionizing radiations are part of our daily life, and when organisms are exposed to them for a long time, they may experience their lethal or sublethal effects. For this reason, technologies have been created to quantify them. In this study, Internet of Things (IoT) was used through connecting gamma meters and a low-cost UV radiation device. The validation of this structure was performed with meters calibrated in certified laboratories. The validation results matched those obtained by the other devices, with an error of 2%.